Mechanical adjuncts for cardiocerebral resuscitation. (2nd September 2019) - Riess, Matthias L.; Balzer, Claudius
ABSTRACT: Introduction : Cardiac arrest remains a worldwide health problem with very poor outcome. In the absence of bystander resuscitation, survival rates decrease by 10% per minute of arrest and global ischemia. Even the best manual chest compressions, however, can only produce a fraction of normal cardiac output and blood flow to vital organs. Physiological principles and current evidence for the use of mechanical devices to increase survival and quality of life after cardiac arrest are highlighted in this review article. Areas covered : Mechanical adjuncts such as the Active Compression Decompression device, automated chest compressors and the use of a negative pressure valve (Impedance Threshold Device) can synergistically aid in improving quality of CPR and increasing cardiac output and vital organ perfusion. Expert opinion : The current conclusions that the use of mechanical adjunct devices in a preclinical setting is not recommended or neutral at best, need to be reevaluated, especially with regard to new advanced and promising treatments that require prolonged high-quality CPR during the transport to a hospital to improve the outcome of patients.